Optimization of Soxhlet Extraction Papaya Seed Oil (Carica papaya L.) with Petroleum Ether - Andriana, Riski; Broto, R. T. D. Wisnu (Journal of Vocational Studies on Applied Research, 2023)
Papaya seed oil is a high source of fatty acids, especially oleic acid, and palmitic acid. It has 71.60% oleic acid, 15.13% palmitic acid, and has a low cholesterol content so it can be useful as a food oil. This study aims to determine the effect of the ratio of ingredients, time, and particle size on the maximum extraction of papaya seed oil. Extraction of papaya seed oil was carried out by the soxhletation extraction method using petroleum ether solvent. The factorial experimental design of 23 was used to determine the significant parameters for the resulting papaya seed oil: yield, density, fatty acid content, viscosity, and water content. The most influential process variable is particle size. The most optimal papaya seed oil extraction results were obtained at a particle size of 20 mesh, an extraction time of 180 minutes, and a ratio of ingredients to the dissolution of 1:9 (35 gram500 mL). That value obtains a yield of 57.029%.